2017
DOI: 10.4142/jvs.2017.18.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation affects the viability and plasticity of equine mesenchymal stem cells: possible implications in intra-articular treatments

Abstract: Mesenchymal stem cells (MSCs) are gaining relevance for treating equine joint injuries because of their ability to limit inflammation and stimulate regeneration. Because inflammation activates MSC immunoregulatory function, proinflammatory priming could improve MSC efficacy. However, inflammatory molecules present in synovial fluid or added to the culture medium might have deleterious effects on MSCs. Therefore, this study was conducted to investigate the effects of inflammatory synovial fluid and proinflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 38 publications
0
19
1
Order By: Relevance
“…The effect of TGF-β2 was dependent on the baseline expression of MHC and donor animals (44). Further in vitro evidence suggests that cytokine priming has a negative impact on the MSCs viability and differentiation when compared to MSCs primed in an inflammatory synovial fluid (45).…”
Section: Mesenchymal Stem Cells Modulate Inflammationmentioning
confidence: 94%
“…The effect of TGF-β2 was dependent on the baseline expression of MHC and donor animals (44). Further in vitro evidence suggests that cytokine priming has a negative impact on the MSCs viability and differentiation when compared to MSCs primed in an inflammatory synovial fluid (45).…”
Section: Mesenchymal Stem Cells Modulate Inflammationmentioning
confidence: 94%
“…The effects of the cytokine priming on equine BM-MSC immunomodulatory and immunogenic profiles, as well as on their viability and differentiation potential, were already described by our group, as those were the same cells than the used in the present study. Briefly, MSC viability was well preserved after proinflammatory priming and under culture with inflammatory synovial fluid (SF) [ 17 , 39 ], as shown by appropriate proliferation, absence of changes in the BAX/BCL-2 ratio and lack of DNA damage. Furthermore, immunomodulatory profile was upregulated in MSC-primed compared to MSC-naïve.…”
Section: Methodsmentioning
confidence: 99%
“…Future studies may need to evaluate MSC galectin protein expression at longer intervals following inflammatory cytokine exposure to confirm that galectin protein expression is not changing significantly. In addition, although the concentrations of pro-inflammatory cytokines tested were similar to those used in prior studies [ 43 , 62 ], it is likely that the concentrations used in this study are much higher than those found in naturally occurring equine OA [ 50 ].…”
Section: Discussionmentioning
confidence: 77%